Fate of Listeria monocytogenes on Fresh Apples under Different Storage Temperatures - Sheng, Lina; Edwards, Katheryn; Tsai, Hsieh-Chin; Hanrahan, Ines; Zhu, Mei-Jun (Frontiers in Microbiology, 2017)
Fresh apples are typically stored for up to 1 year commercially; different apple varieties require different storage temperatures to maintain their quality characteristics. There is sparse information available about Listeria monocytogenes survival on fresh apples under various storage temperatures. The objective of this study was to comprehensively evaluate the effect of storage temperature on apple fruit decay and L. monocytogenes survival. Unwaxed apple fruits of selected varieties (Fuji and Granny Smith) were dip inoculated in a three-strain L. monocytogenes cocktail to establish ∼3.5 and 6.0 Log10 CFU/apple. Twenty-four hours post-inoculation, apples were subjected to 1, 4, 10, or 22°C storage for up to 3 months. Apples under the different storage treatments were sampled at 1-, 4-, 7- and 14-day for short-term storage under all four tested temperatures, and 2-, 4-, 8-, and 12-week for long-term storage at 1, 4, and 10°C. A set of uninoculated and unwaxed apples were simultaneously subjected to the previously mentioned storage temperatures and sampled biweekly for their total bacterial count (TPC) and yeasts/molds (Y/M) count. During the 2-week short-term storage, L. monocytogenes population on organic Granny Smith apples stored at 1, 4, or 10°C was reduced by 0.2–0.3 Log. When apples were stored at 22°C, there was a 0.5–1.2 Log10 CFU/apple reduction 14-day post storage dependent on the initial inoculation level. During the 12-week cold storage under 1, 4, and 10°C, L. monocytogenes count on organic Granny Smith apples decreased by 0.5–1.5 Log10 CFU/apple for both inoculation levels. L. monocytogenes had similar survival pattern on conventional Granny Smith and Fuji apples with 0.8–2.0 Log10 CFU/apple reduction over a 3-month cold storage period. Interestingly, both TPC and Y/M count were stable regardless of apple variety or cultivation practice during the 12-week storage at all tested temperatures. In summary, while L. monocytogenes did not proliferate on apple surfaces during 12 weeks of refrigerated storage, only a limited reduction of L. monocytogenes was observed in this study. Therefore, the apple industry cannot rely on cold storage alone to control this pathogen. Additional interventions are needed to eradicate Listeria on fresh apples during long-term cold storage.